LEKSIKON PERPADIAN DALAM MASYARAKAT DAYAK JALAI DI KABUPATEN KETAPANG - Gunawan Kardi; Sisilya Saman Madeten; Agus Syahrani (Universitas Tanjungpura, 2019)
AbstractThis study view on lexicon of rice in the Dayak Jalai Society in Ketapang Regency. Rice is everything related to rice farming activities in the community. The problem in this study was regarding the grouping of the lexicon of rice, semantic relations, and the level of understanding of the noun, verb and adjective lexicon. The method used was descriptive with a form of qualitative research. The data source was the informant and the data was in the form of a lexicon regarding the rice in the Dayak Jalai community. The technique used was an interview while the data collection tool was in the form of a recording device and a camera from a cell phone, pens and notebooks. Based on the results of the analysis found that 100 data lexicon of rice that which is divided into 16 claisifications parts of rice plants, animals disturbing, plants disturbing, rice farming process, traditional supplementary materials, tools for customary ritual activities, time for carrying out farming and traditional rituals data, characters in traditional rituals, objects related to rice, tools for cleaning land, soil type, rice type, rice planting tool, harvesting tool, paddy grooves become rice, and tools make paddy into rice. Key words: Dayak Jalai Ketapang, Lexicon, Rice